CHANGES IN THE TONGUE MUCOSA OF RATS IN THE LONG-TERM OF EXPERIMENTAL DIABETES MELLITUS - Жураківська, О. Я.; Атаманчук, О. В.; Міськів, В. А.; Костіцька, І. О.; Жураківський, В. М.; Дутчак, У. М.; Гречин, А. Б.; Клипич, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The work is dedicated to the study changes in the tongue mucus in the long-term course of streptotrozine diabetes mellitus. 40 sexually mature white rates (body weight 180) were divided into two groups for the study: experimental and control. Experimental group (30 rats) was administered intraperitoneally intravenously streptozotocin "SIGMA" (USA), which was diluted in 0.1 M citrate buffer with pH 4.5 (at the calculation of 6 mg per 100 g body weight), in control group in equivalent dose were injected only the citrate buffer. Smears-prints on sterile objective glasses were painted by Romanovsky-Gimza. for study the cytological characteristics of the mucous membrane of the tongue (MMT), The method of scanning electron microscopy was used. Hypertrophic changes in the papillomas of MMT, enlargement of the pore of taste bulbs can be traced according to scanning electron microscopy in six to eight weeks of streptozotocin-induced diabetes mellitus with a pronounced increase in glucose and glycated hemoglobin concentrations. The number of microflora on the background of reducing the adsorption capacity of epithelial cells and a small number of leukocytes increases according to the cytological study smears-reflections MMT, and the cell differentiation index is reduced by 31.5%, respectively (p <0.05). The keratinization index in the 8th week of the experiment decreases to 58.9 ± 3.56, compared with the previous experiment and control (p <0.05), which indicates a violation of the processes of differentiation of epithelial cells and the deposition of deeper layers of MMT. So, the stage of destructive processes can be identified in the long-term flow of streptozotocin diabetes, this stage is manifested by a significant morphological rearrangement of MMT with conformation of different papillae and a decrease in the adhesive properties of epithelial cells.